Expression and polymorphism of micro‐RNA according to body mass index and breast cancer presentation in Tunisian patients. Issue 2 (10th October 2018) - Belaiba, Fadoua; Medimegh, Imene; Ammar, Meriem; Jemni, Feriel; Mezlini, Amel; Romdhane, Khaled Ben; Cherni, Lotfi; Benammar Elgaaïed, Amel
Abstract: Micro‐RNAs (miRs) constitute a class of small noncoding RNAs implicated in the regulation of gene expression by binding to target mRNAs. A miR can target several mRNAs, being involved in different biologic processes and pathologies. This pleiotropic function might explain the link between diseases co‐occurrence. Epigenetic origin of the link between obesity and breast cancer (BC) is investigated in a cohort of Tunisian patients, focusing on polymorphism at germline level (miR‐146a) and on expression in mammary tumors (miR‐21, miR‐146a, and miR‐34a), according to body mass index (BMI) and clinico‐pathologic features. The measure of miR expression in 60 mammary tumors was realized using quantitative RT‐PCR. Study of rs 2910164 in miR‐146a was performed by PCR and direct sequencing using blood DNA of 83 affected women and 50 unrelated subjects from Great Tunis. MiR‐21, miR‐146a, and miR‐34a have been quantified in breast tumor according to BMI. MiR‐21 is significantly more expressed in tumors of obese women comparatively to nonobese patients. On the contrary, miR‐34a is decreased in tumors of obese women. Moreover, in obese BC patients, a significant increase in both miR‐21 and miR‐146a expression is revealed in cases with lymph node metastasis. The polymorphism at rs 2910164 (miR‐146a) locus was not shown as a risk factor for BC. However the mutant CC genotype was revealed to be associated with a risk for bad outcome of the disease. Chronic inflammation in obese women would be linked to aggressive breast tumors via induction of oncomiRs overexpression and decrease of tumor suppressor miRs. Abstract : Chronic inflammation in obese women is linked to aggressive breast tumors via induction of oncomiR over‐expression and decrease of tumor suppressor miR.